Failure Analysis of Sludge Centrifuge Separator Machine Using Root Cause Analysis (RCA) at PT. X - Nuraini Rahmad; Arsi, Fadli; Oktaviya, Trisna Dwi (Journal of Engineering Science and Technology Management (JES-TM), 2025)
The palm oil processing industry is expanding rapidly, as seen from the increasing land conversion for oil palm plantations. One critical machine in the production process is the sludge centrifuge separator, which functions to separate oil from sludge. At PT. X, a breakdown in this machine disrupted production and reduced the effectiveness of oil separation. This study aims to identify the causes of damage or failure in the sludge centrifuge separator machine. The research employs Root Cause Analysis (RCA) with a fishbone diagram as the analytical tool and proposes improvements using the 5W+1H approach.The results show that damage is caused by several factors. Human factors include operator negligence, lack of discipline, and inadequate supervision. Machine-related issues involve poor maintenance, leaks, insufficient inspections, bearing wear, and excessive friction. Material factors include the entry of metal pieces and small stones into the machine. Method-related problems stem from non-compliance with SOPs and insufficient training. Environmental factors include damp conditions, poor air circulation, oil spills, noise, and an unclean production floor.This research highlights the importance of regular maintenance, improved training, strict SOP implementation, and better workplace management to minimize machine failure and ensure optimal.